Mental and Emotional Experiences among Registered Nurses during SARS COV-2 Pandemic: A Meta-Synthesis - Manish Kumar Balai; V. A. Raghu; Dutt Avasthi Rishi; Ram Bishnoi Hanuman (Indian Journal of Psychiatric Nursing)
The pandemic COVID-19 has exposed the nurses to tough and emotionally stressful working environment which could affect the mental health which results, delivery of poor quality of patient care, increase the medical error, and higher turnover of nurses. The aim of this meta-synthesis was to synthesize the mental and emotional experiences of nurses while caring for COVID-19 patients. This meta-synthesis was done according to the Preferred Reporting Items for Systematic Reviews and meta-Analysis guidelines 2021. Literature was searched from Google scholar, Scopus, PubMed, MEDLINE, and CINAHAL electronic database using the Medical Subject Heading words. The meta-synthesis reported data from 10 phenomenological studies with 198 nurses as informants of which 122 were female and 40 were male and the remaining 36 sample categories were not reported and their mean age was 29.62 years. The thematic analysis was performed to derive the six major themes which include negative emotion, optimism, adaptation to the COVID-19 pandemic, health-care concern, somatic experience, and professional obligation with 12 subthemes. The outcome of the meta-synthesis was that nurses experienced fear, anxiety, hopelessness, somatic symptoms, fatigue, and heavy workload due to inadequate training, shortage workforce, and unpreparedness. The authors suggest adequate preparedness of nurses to face any hardship of future pandemic